The Effects of Capital Structure and Corporate Social Responsibility towards Firm’s Value - Nuryaman; Oktaviana Saleh, Saphira; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Every company must have a long-term goal, namely to prosper the shareholders. This method is taken by maximizing the value of the company. The purpose of this study was to determine the effect of capital structure and disclosure of corporate social responsibility on the value of the company. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. The population size of this study is 155 manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. The sample collection technique in this study was 83 manufacturing companies listed on the Indonesia Stock Exchange. The type of data used is secondary data originating from the official website of the Indonesia Stock Exchange and the website of each company. The results of this study prove that partially the capital structure and disclosure of corporate social responsibility affect the value of the company. While simultaneously the capital structure and disclosure of corporate social responsibility have an influence on the value of the company. Suggestions for future researchers are to add research model variables that have an influence on company value.